QoS guaranteed resource block allocation algorithm in LTE downlink - Zhao, Liqun (2013)
Long term evolution (LTE) is the next generation wireless communication network which is an all-IP based system. Nowadays, more and more kinds of services are being transmitted on wireless communication network with different requirements. So, to satisfy the quality of service (QoS) of multi-service requirements is one of the key challenges that need to be dealt in the LTE system. In this paper, we propose a cross layer solution called token bucket scheduler (TBS) for real time service that allocates resource block (RB) for different services in order to meet their QoS requirements. TBS utilizes instantaneous downlink channel signal to interference plus noise ratio (SINR) and service QoS information when determining whether a RB allocates to a real time service. Through extensive simulations, the results show that TBS algorithm greatly improves throughput, delay and packet loss ratio compared with the maximum-largest weighted delay first (M-LWDF) scheduling algorithm and exponential/proportional fair (EXP/PF) scheduling algorithm in real time service.